New laser power sensor using weighing method. (12th December 2017) - Pinot, P; Silvestri, Z
Abstract: We present a set-up using a piece of pyrolytic carbon (PyC) to measure laser power in the range from a few milliwatts to a few watts. The experimental configuration consists in measuring the magnetic repulsion force acting between a piece of PyC placed on a weighing pan and in a magnetic induction generated by a magnet array in a fixed position above the PyC sheet. This involves a repulsion force on the PyC piece which is expressed in terms of mass by the balance display. The quantities affecting the measurement results have been identified. An example of metrological characterization in terms of accuracy, linearity and sensitivity is given. A relative uncertainty of optical power measurement for the first experimental set-up is around 1%. The wavelength and power density dependence on power response of this device has been demonstrated. This PyC-based device presented here in weighing configuration and the other one previously studied in levitation configuration offer a new technique for measuring optical power.